2016
DOI: 10.1037/pag0000099
|View full text |Cite
|
Sign up to set email alerts
|

When the mind wanders: Distinguishing stimulus-dependent from stimulus-independent thoughts during incidental encoding in young and older adults.

Abstract: In recent years, several studies have indicated that healthy older adults exhibit a reduction in mind-wandering compared to young adults. However, relatively little research has examined the extent to which ongoing thoughts in young and older adults are dependent on environmental stimuli. In the current study, we assessed age-related differences in frequency of stimulus-dependent thoughts (SDTs) and stimulus-independent thoughts (SITs) during a slow-paced incidental encoding task. Based on previous research su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(81 citation statements)
references
References 60 publications
6
73
1
1
Order By: Relevance
“…The retrospective bias reported in the present study by the Verbal-cues group is consistent with the evidence coming from direct comparisons between involuntary memories and involuntary future thoughts (Berntsen & Jacobsen, 2008): although both involuntary memories and involuntary future events were found to be mainly triggered by clearly identifiable cues, external cues were more frequent for involuntary memories than for involuntary future events (52% vs. 34% in Berntsen & Jacobsen, 2008). In a similar vein, in a very recent study on MW in elderly and young adults, Maillet and Schacter (2016b) found that environmental stimuli (cues) primarily triggered past-oriented thoughts. These results are consistent with the fact that, compared to memories, involuntary future thinking is related to and triggered primarily by current concerns, being less dependent from external stimulation (Cole & Berntsen, 2015;Klinger, 2013).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The retrospective bias reported in the present study by the Verbal-cues group is consistent with the evidence coming from direct comparisons between involuntary memories and involuntary future thoughts (Berntsen & Jacobsen, 2008): although both involuntary memories and involuntary future events were found to be mainly triggered by clearly identifiable cues, external cues were more frequent for involuntary memories than for involuntary future events (52% vs. 34% in Berntsen & Jacobsen, 2008). In a similar vein, in a very recent study on MW in elderly and young adults, Maillet and Schacter (2016b) found that environmental stimuli (cues) primarily triggered past-oriented thoughts. These results are consistent with the fact that, compared to memories, involuntary future thinking is related to and triggered primarily by current concerns, being less dependent from external stimulation (Cole & Berntsen, 2015;Klinger, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, in the study by Mazzoni et al (2014) more IAMs were elicited when verbal cues were presented during the task, rather than pictorial cues, whereas there was no significant difference between the effects of verbal and pictorial cues on the non-memory contents. As recently suggested by Maillet and Schacter (2016b), the strong association between environmental cues and past-events might be a very important adaptive mechanism that helps people relate the current environment to similar situations experienced in the past and this might support appropriate behavior (Preston & Eichenbaum, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, whereas current evidence suggests that older adults do not mind-wander more than young adults during cognitive tasks (thoughts that have nothing to with, and were not triggered by any stimulus the current task, such as dinner plans), one possibility is that they exhibit more task-related thoughts and feelings (thoughts/feelings triggered by stimuli in the task itself, such as a picture of a sofa triggering a thought about how it looks similar to the one in my living room) [12]. Distinguishing which thoughts are task-related/unrelated is a thorny issue, and may vary based on the specific requirements of a task.…”
Section: Cognitive Processes Associated With Reduced Deactivations Inmentioning
confidence: 99%
“…. Accordingly, Maillet and Schacter (2016b) have made a useful distinction between stimulus-dependent and stimulus independent mind-wandering and have provided initial empirical evidence for potential differences between the two (see Maillet et al, 2017). 5 Consequently, in the present study we have investigated the effects of aMCI status on stimulus-dependent (but spontaneous) mind-wandering, given that instances of stimulusindependent mind-wandering (i.e., instances of task-unrelated thoughts with no reported triggers) were relatively low in both groups.…”
Section: Cdr-based Classification Used By Gyurkovics Et Al (2017) Amentioning
confidence: 99%